Experiência e formação: o fazer teatral nas trajetórias docentes - Andrea Maria Favilla Lobo (2010)
This study addresses the training of teachers who work with theater in art classes in schools of the second segment of the State Primary and High School, in the urban area of Rio Branco, capital of the State of Acre. It is part of the field of research on teacher education and schooling in theater, discussing both approaches: theater in school and also the possible relationships between the spaces of education, ie, college, school, theater space and the processes of socialization of these teachers. The main objective of this research is to investigate the reasons why the art teachers of public schools, in elementary and high school, who develop drama activities, became teachers in this field, identifying and discussing the formative process as well as the concepts that guide their work, making reference to the theories of teaching drama and curriculum guidelines for Basic Education in theater Sub-area. Understand the aspects that underlie the choices and preferences of teachers, from the theoretical perspective of Pierre Bourdieu, Bernard Lahire and Cultural History, as well as discussing the teachers knowledge and conceptions of theater, from their training trajectories. The research is divided into two stages: at the first stage, focused on quantity, questionnaires were filled by the population of teachers who work with arts in State Basic Education Schools of the urban zone of Rio Branco, Acre. Also discussed were the concepts present in the National Curriculum on theater teachers. In the second stage, qualitative, there were three types of interviews with teachers selected in the first part of this study. Data were analyzed by categories built later in relation to the theoretical framework discussed. The categorization enabled the raising of issues: the identification with the female figure and the choices for teaching, the knowledge of experience in theatrical practices in school and the construction of preferences.